УЛОГА УПРАВЕ У ПОСТУПКУ ВРАЋАЊА ЗАДРУЖНЕ ИМОВИНЕ - Milkov, Dragan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
According to the Law on Cooperatives of 1990 property that was owned by cooperatives and associations of cooperatives after 01 July 1953, and which is through organizational and statutory changes or otherwise transferred without compensation to other users who are not cooperative or cooperative associations will be returned to the same types of cooperative whose property had been, and if there is none, then the cooperative of the same type operating in the area in which it operated cooperative that owned the property for which restitution is requested. Such a provision is in practice led to numerous problems. On the one hand, the return of confiscated property represents redress, if they meet all legal requirements. But on the other hand, the law leaves room for abuse. It is possible that the property "returns" to persons who are subsequently formed a cooperative in the same area, as the legal successor does not exist and that it should be given to assets with which they have no legal or real connection. It is therefore necessary to interpret restrictively the conditions for the return of cooperative property and take into account the inviolability of private property if the property of cooperative has become with compensation someone's private property. In any case, the right to return can only belong to entities that have some kind of legal succession with the cooperative of which property was confiscated.